Pengaruh Edupreneurship, Kreativitas Siswa dan Praktik Pengalaman Industri Terhadap Minat Berwirausaha Siswa di SMK Negeri 1 Enam Lingkung - Devi Hariyani; Syamwil Syamwil (Universitas Negeri Padang, 2022)
This research aims to determine the effect of edupreneurship, creativity and student feel experience of students interest in entrepreneurship at SMK Negeri 1 Enam Lingkung. This type of research is associative. The population in this study were year 12 students at SMK Negeri 1 Enam Lingkung and the number of samples using the Slovin formula was 73 samples. Data was collected by distributing questionnaires to year 12 students with predetermined criteria. The data will be analyzed using multiple regression analysis. The results showed that (1) edupreneurship, creativity and student feel experience had a significant and positive effect on student entrepreneurship interest at SMK Negeri 1 Enam Lingkung with a significant level of 0,000 < 0,05 (2) edupreneurship had a significant effect and positive on student entrepreneurship interest at SMK Negeri 1 Enam Lingkung with a significant level of 0.000 < 0.05 (3) creativity had a significant and positive effect on student entrepreneurship interest at SMK Negeri 1 Enam Lingkung with a significant level of 0.006 < 0.05 (4) the practice of student feel experience had a significant and positive effect on student entrepreneurship interest at SMK Negeri 1 Enam Lingkung with a significant level of 0.028 < 0.05